Social Support, Self-Esteem and Quality of Life among People Living With HIV/AIDS in Jammu & Kashmir India - Wani, Mohammad Amin (Anales de Psicología / Annals of Psychology, 2020)
Background: The cardinal aim of the present study was to assess the level of social support, self esteem and quality of life among people living with HIV/AIDS in Jammu and Kashmir State of India. Further, the study strived to explore the relationship between independent and dependent variables. Method: The study consists a sample of 460 AIDS patients selected through purposive sampling technique, out of them 177 (38.3%) were male, 283 (61.5%) were female patients; 295 (64.1%) were married and 165 (35.9%) were unmarried. Measures included Enriched Social Support Inventory by Mitchell et al., (2003), Rosenberg's Self-Esteem Scale (1965) and Quality of Life Scale by Sharma & Nasreen (2014). For the statistical analysis of data Mean, Standard deviation, Frequency distribution, t-test, one way analysis of variance, correlation analysis and Scheffe’s post hoc test was applied by SPSS 20.0 version. Findings: The findings illustrated that majority of patients have poor social support, lower self-esteem and poor quality of life; also it reveals that patient’s social support, and self-esteem differs by age, occupation, duration of illness, gender, and marital status. However their quality of life differs only by their age, occupation, duration of illness, and marital status. Further the result shows social support and self-esteem are positively correlated with quality of life.